2014
DOI: 10.1002/tox.21964
|View full text |Cite
|
Sign up to set email alerts
|

The influence of humic acid on the toxicity of nano‐ZnO and Zn2+ to the Anabaena sp.

Abstract: This study explored the effects of humic acid (HA) on the toxicity of ZnO nanoparticles (nano-ZnO) and Zn(2+) to Anabaena sp. Typical chlorophyll fluorescence parameters, including effective quantum yield, photosynthetic efficiency and maximal electron transport rate, were measured by a pulse-amplitude modulated fluorometer. Results showed that nano-ZnO and Zn(2+) could inhibit Anabaena sp. growth with the EC50 (concentration for 50% of maximal effect) of 0.74 ± 0.01 and 0.3 ± 0.01 mg/L, respectively. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…ZnO at 100 ppb-163 ppm, QDs at 60-3600 ppb). 26,27,29,[51][52][53] Finally, this method does not require the commonly employed feature (e.g. optical emission) for fluorescent ENPs such as QDs, which photoluminescent properties can easily be quenched.…”
Section: Analytical Performances: Qd-loq and Precisionmentioning
confidence: 99%
“…ZnO at 100 ppb-163 ppm, QDs at 60-3600 ppb). 26,27,29,[51][52][53] Finally, this method does not require the commonly employed feature (e.g. optical emission) for fluorescent ENPs such as QDs, which photoluminescent properties can easily be quenched.…”
Section: Analytical Performances: Qd-loq and Precisionmentioning
confidence: 99%
“…To summarize our results for the QD-LOQs, the mean values of the QD-LOQs for Cd and Zn are 15 and 3132 ppt, respectively. These values are lower than the typical concentrations used in ENP dissemination and toxicity studies (ppb-ppm level) 18,[33][34][35] . Indeed, coherent to our previous findings in the case of aquatic matrices, the QD-LOQs found on average previously were also lower by about 3 to 6 orderof magnitudes than those in the aforementioned studies.…”
Section: Qd-loqs and Precisionmentioning
confidence: 68%
“…Based on our findings, isotopic labelling of ENPs coupled with HR-ICP-MS will enable researchers to work at ENP concentrations lower than the usual range of concentrations used in ENP studies related to their fate, behavior, and toxicity (e.g. QDs at 60-3600 ppb) 33,34 . In addition, this method does not require the use of specific ENP characteristics (e.g.…”
Section: Qd-loqsmentioning
confidence: 94%
“…Interestingly, the presence of recalcitrant components of EPS such as humic-like acids can reduce the bioavailability of contaminants to organisms due to the increased electrostatic repulsion (Lundqvist et al, 2010;Tang et al, 2015). A decrease in the selenium uptake by plant roots due to interactions between selenite and fulvic acids was reported (Wang et al, 1996), and it was suggested that association of selenium with organic matter in aquatic environments may play an important role in the mobility and bioavailability of selenium.…”
Section: Effect Of Eps On Nano-se Toxicitymentioning
confidence: 99%